(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Mahmoud Amin Al-Alam aims in this research to reveal the backwardness, dependency, and marginalization that the Arab reality suffers today at all levels by global capitalism, in addition to the crises, exploitation, injustice and extension of its colonial expansion all over the world. Through its invention of a fictitious history of the West, full of progress, development, achievements, civilizations, and distinguished culture in contrast to the history of Arab backwardness and making them in a state of permanent dependence, which will lead us to question the relationship of the ego to the other and how to get out of the crucible of the superior Western and the Eastern subordinate. I will try as much as possible to intensify the ideas to clarify the opinion of Mahmoud Amin Al-Alam regarding the relationship of the ego to the other and the way he rejects the hostile duality between them, and the advantages of each, and what is the alternative to that dualism which is nothing but an attempt to exclude and deny the other and highlight its negatives until the unique ego emerges.